Reproducibility of Histologic Assessment in Porto-sinusoidal Vascular Disease Liver Biopsies. (28th October 2020) - Kmeid, M; Lee, H; Lagana, S M; Lin, J; Affolter, K; Choi, W; Liu, X; Choi, K E; Westerhoff, M; Yang, Z; Fiel, M
Abstract: Introduction/Objective: Variable histologic findings that may be seen in porto-sinusoidal vascular disease (PSVD) liver biopsies are subject to high interobserver variability, requiring correlation with clinical history of portal hypertension (traditionally interpreted as non-cirrhotic portal hypertension NCPH). We investigated which histologic features are reproducible in PSVD biopsies. Methods: Archived liver biopsies (n=38) from patients with NCPH (n=14) and without NCPH (n=21) were reviewed. Static H&E images of lobules (L, x100, NCPH=27, non-NCPH=23) and portal tracts (P, x200, NCPH=23, non- NCPH=27) were distributed among 9 gastrointestinal pathologists blinded to clinical history. Each pathologist answered multiple choice questions based on the presence (Q2) or absence (Q1) of portal hypertension clinically. The choice selected by 6 pathologists or more was considered consensus answer for the image. The interpretation of the image was considered reproducible when consensus was reached on both Q1 and Q2. Results: The interpretations of 27 (54%; 17L, 10P) images from NCPH and 21 (42%; 10L, 11P) from non-NCPH were reproducible. In NCPH, the interpretations of normal (n=10, 4L, 6P), sinusoidal dilatation (n=7), and increased parenchymal draining vessels (n=3) were reproducible, while there was no consensus on the diagnoses of nodular regeneration and increased number of portal vessels. In non-NCPH, the interpretations of normal (n=8, 2L, 6P), sinusoidal dilatation (n=6), and paraportal shunting vessel(s) (n=4) were reproducible, whereas no consensus was reached on the diagnoses of nodular regeneration, incomplete fibrous septa, and increased number of portal vessels. Conclusion: Histologic assessment of normal L and P as well as sinusoidal dilatation appears to be reproducible independent of clinical history. The findings of increased parenchymal draining vessels in NCPH group and paraportal shunting vessels in non-NCPH group may be consistently diagnosed to a certain extent. The assessment for nodular regeneration without reticulin stain, incomplete fibrous septa, or increased number of portal vessels appears to be unreliable.